(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article analyzes the role and significance of nurses in ensuring continuous care for oncology patients. The aim of the study is to substantiate the clinical, psychological, and social functions of nurses in the care of cancer patients. Analytical, comparative, and systematic research methods were employed. The findings indicate that nurses play a key role in supporting patients throughout the treatment process, preventing complications, and improving quality of life. The results of the study are of practical importance for improving nursing practice in oncology settings.